EUGENOL AMELIORATES RHABDOMYOLYSIS-INDUCED ACUTE KIDNEY INJURY IN MICE - Nadia Saifullah; Zahida Memon; Rehan Ahmed Siddiqui; Moazzam Ali Shahid; Talat Mirza (ziauddin University, 2024)
ABSTRACT   Background: Acute kidney injury (AKI) is a common and dangerous consequence of rhabdomyolysis which occurs in 50% of the cases with 5-10% mortality. In recent studies, eugenol has been reported as anti-fungal, antihyperglycemic, analgesic, anti-bacterial, anti-pyretic, anti-inflammatory and anti-oxidant agent. This study aimed to investigate the protective activity of eugenol on rhabdomyolysis-induced acute kidney injury (AKI) in mice.   Methods: Male, 24 BALB/c mice were divided into 4 groups (controls, AKI, eugenol and ascorbic acid as positive control). Controls and AKI were given normal saline, Eugenol (100 mg/kg bw) and ascorbic acid (200mg/kg) were given orally eugenol and ascorbic acid respectively for four days. After water deprivation for 24 hours, all animals, except controls, were injected with glycerol (50% - 10 ml/kg body weight intra-muscularly). After another 24 hours, blood samples were collected and kidneys were dissected out for biochemical investigations (serum urea and creatinine) and histopathological examination.    Results: Serum urea and creatinine levels compared to controls were significantly elevated in AKI group (p < 0.001) and significantly decreased, in eugenol and ascorbic acid groups (p < 0.001) compared to AKI group.  Histopathological examination revealed about 44% damage in the AKI group compared to the normal group (p < 0.001). Eugenol and ascorbic acid decreased the damage to 13% and 8% respectively compared to AKI group (p < 0.001). The tested compounds were found to reduce tubular cast formation. Conclusion: Eugenol has protective effects on rhabdomyolysis-induced AKI in mice. Further studies are required for evaluation of protective role of this compound in AKI.